Implementasi Network Attached Storage (NAS) Menggunakan Synology Disk Station Manager (DSM 5.2) Untuk Optimalisasi Data Sharing Center - Sidik Sidik; Muhammad Putra (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
Along with the development of technology, especially computer and internet, we can get information more easily. It also encourages the number of computer users and the internet is getting bigger. Especially in the environment of PT. Prism Dynamics Indonesia, the number of employees who use the internet more and more from time to time. Increasing users who use the network will cause the existing network infrastructure, should be increased so as not to make users disappointed due to decreased network performance. At PT. Prism Dynamics Indonesia a lot of important files that must be stored starting from the data project, finance, sales, purchasing and service of goods, all hardcopy data or softcopy if not stored properly then there will be damage to the data or even lost. it takes a centralized data storage container like file sharing. File sharing is a system where many users can share files and storage resources with a client-server concept run over the network. A file server allows users to share information over a network without having to physically send files with floppy disks or some other external storage device.